The sources of social power - Mann, Michael (Cambridge University Press, 2012)
Distinguishing four sources of power in human societies ? ideological, economic, military and political ? The Sources of Social Power traces their interrelations throughout human history. In this first volume, Michael Mann examines interrelations between these elements from neolithic times, through ancient Near Eastern civilizations, the classical Mediterranean age and medieval Europe, up to just before the Industrial Revolution in England. It offers explanations of the emergence of the state and social stratification; of city-states, militaristic empires and the persistent interaction between them; of the world salvation religions; and of the particular dynamism of medieval and early modern Europe. It ends by generalizing about the nature of overall social development, the varying forms of social cohesion and the role of classes and class struggle in history. First published in 1986, this new edition of Volume 1 includes a new preface by the author examining the impact and legacy of the work.
Includes bibliographical references and index.
Keywords: Social history; Power (Social sciences); Social evolution; Social classes -- History; Nation-state -- History